Late Surgical Site Infection in Immediate Implant-Based Breast Reconstruction - Sinha, Indranil (Plast Reconstr Surg, 2017)
INTRODUCTION: Surgical site infection (SSI) can cause devastating reconstructive failure in implant-based breast reconstructions. Many large national database studies have offered insights into complication rates, but only capture early outcomes within 30-days post-operatively. This study evaluates both early and late SSI in immediate implant-based reconstruction and identifies predictors. METHODS: As part of the Mastectomy Reconstruction Outcomes Consortium Study (MROC), 1662 implant-based breast reconstructions in 1024 patients were evaluated for early vs. late SSI. Early SSI was defined as infection occurring within 30 days post-operatively and late SSI as infection occurring 31 days to 1 year. Minor infection required oral antibiotics only, and major infection required hospitalization and/or surgical treatment. Direct-to-implant (DTI) patients had one-year follow-up, and tissue-expander (TE) patients had one-year post-exchange follow-up. RESULTS: Among 1491 TE and 171 DTI reconstructions, overall SSI rate for TE was 5.7% (85/1491) after first-stage, 2.5% (31/1266) after second-stage, and 9.9% (17/171) for DTI. Over 47–71% of SSI complications occurred as late SSI. Multivariate analysis identified radiotherapy and BMI as significant predictors of late SSI. No significant difference between DTI and TE group in the occurrence of early, late, or overall SSI was found. CONCLUSIONS: The majority of SSI complications in immediate implant-based breast reconstructions are late infections occurring more than 30 days following both first-stage and second-stage procedures. Radiotherapy and obesity are significantly associated with late-onset SSI. Current studies limited to early complications do not present an accurate or complete assessment of infection complications associated with implant-based breast reconstructions or their long-term clinical outcomes.